Recent Investigations of Mission Period Activity on Sapelo Island, Georgia - Richard W. Jeffries; Christopher R. Moore (Journal of Global Initiatives, 2011)
Prior to their retreat to Florida in 1684, Muskogean-speaking Guale Indians inhabited much of what is now the Georgia coast. The arrival of Spanish missionaries in Florida and Georgia in the mid-1500s began what is known archaeologically as the mission period (1568-1684), a time of sustained interaction between the Spanish and the Guale people. Over time, population loss due to European-introduced diseases and conflict with English-backed Native American slave raiders resulted in a drastic reconfiguration of Guale society and the abandonment of the Guale's ancestral homeland (Worth 2007).